Fluorimetric Determination of Mefenamic Acid using Sodium Per Sulfate as a Precipitating Agent and Low Pressure Mercury Lamp; Via the use of ISNAG Continue Flow Fluorimeter - Nagam Shakir Turkie (Journal of Global Pharma Technology, 2019)
A new, simple, sensitive and fast method for the determination of Mefenamic acid in pure form and drugs (tablets) by continuous flow injection analysis via measurement of diverged beam of light by ISNAG_-fluorimeter. The method based on the reaction of the Mefenamic acid with sodium persulfate to form yellow precipitate. Optimum parameters have been studied to increase the sensitivity for the developed method. The linear dynamic range for the instrument response versus Mefenamic acid concentration was 0.01-5 mmol/L while the L.O.D was 215.955 ng/sample from the step wise dilution for the minimum concentration of lowest concentration in the linear dynamic range of the calibration graph. The correlation coefficient (r) was 0.9968 while percentage linearity (R2%) was 99.35%. RSD% for the repeatability (n=8) was lower than 0.2% for the determination of Mefenamic acid, with concentration of 1, 3 mmol/L respectively. The: developed method was applied successfully for the determination of Mefenamic acid in pharmaceutical tablets. A comparison was made between the newly developed methodology and the classical method (turbidometry) of analysis using the standard addition method via the use of paired t-test. It shows that there was no significant difference between the quoted values of each individual company with calculated t-value at 95% confidence interval from developed method.Keyword: Mefenamic acid, Flow injection analysis, Diverged beam of light, Homemade instrument.